The responsibilities of the health personnel at pharmacovigilance system [İlaç güvenliliǧi izleminde saǧlik mesleǧi mensuplarinin rolü] - (:unkn) unknown (My University, 2008)
Pharmacovigilance is the process of; i) screening medicines as they are used in everyday practice and in clinical research to identify previously unrecognized or changes in the patterns of their adverse effects, ii) assessing the risks and benefits of medicines in order to determine what action, if any, is necessary to improve their safe use, iii) evaluating the drug safety at the national and international levels, iv) providing information to users to optimize safe and effective use of medicines, v) monitoring the impact of any action taken. New drugs are only marketed after carefully controlled clinical trials have shown them to be sufficiently safe and effective, but this system does not have enough sensitivity for the detection of adverse events that appear only after the uncontrolled use of the marketed drug in large numbers of heterogeneous patients, in contrast to the carefully controlled use in limited numbers of relatively homogeneous patients enrolled in trials. Therefore, drugs should be closely monitored by a national pharmacolovigilance system after postmarketing. The new establishment and the management of pharmacovigilance system at the Turkish Ministry of Health and the responsibilities of the health personel are reviewed.